Compressive Strength-Ultrasonic Pulse Velocity Relationship of Concrete Containing Plastic Waste. Issue 1 (November 2020) - Mohammed, Azad A.
Abstract: In this paper the relationship between compressive strength and non-destructive behavior of ultrasonic pulse velocity (UPV) of concrete containing different plastic wastes has been investigated. For this purpose, a total of 102 data observations were collected from nine past works on properties of concrete with plastic waste and analyzed. Relationship between both compressive strength and UPV with plastic waste aggregate was found weak. Also, relationship between compressive and UPV is not strong, and in contrast, there is a relatively strong correlation between compressive strength ratio (concrete with plastic waste/control concrete) and UPV ratio. Using regression analysis, an equation was developed for calculating compressive strength of concrete with plastic waste depending on the UPV test data. The proposed equation is helpful to assess the residual compressive strength and consequently the structural health monitoring of those structures made of concrete with aggregate partially replaced with plastic wastes, which depends essentially on test data of UPV and compressive strength of control concrete.